Effectiveness of positive education on well-being, character strengths and optimism of students - Sorayyā Hakimi; Siāvash Tālepasand; Zahrā Sājedi (فصلنامه نوآوری‌های آموزشی, 2018)
Positive psychology is the scientific study of human flourishing and a practical approach to optimize the individual’s life. The aim of this study was to evaluate the effects of positive education on well-being, character strengths and optimism of ninth grade students. Participants included 46 female ninth grade public school students. To select the sample, two schools were randomly selected from among the 1st cycle secondary schools of Tehran. The students selected from one school were considered as experimental group (n=22) and the students selected from the other school were considered as control group (n=24). Participants in both groups completed the questionnaires of well-being, character strengths and optimism. Then, positive education was performed in the experimental group. Data were analyzed using multivariate analysis of variance model. The results showed that the level of well-being in the experimental group was significantly higher than the control group after intervention (Eta=0.32). Besides, the character strengths of students in the experimental group were significantly enhanced in which the most effect was on transcendence virtue (Eta=0.68) and the least effect was on temperance virtue (Eta=0.52). However, this intervention had no significant effect on optimism. It could be concluded that positive education was able to increase significantly the level of well-being and character strengths of students. In addition, findings of this research on positive education showed that teaching the positive psychological skills to students and incorporating these skills into school curriculum will result in mental health and educational improvement of students.